Respuesta :
Answer:
-x
Step-by-step explanation:
12 5/6=77/6
77/6x-14x+1/6x
77/6x+1/6x-14x
78/6x-14x
78/6x-84/6x
-6/6x
-x
The result of the given expression 12 5/6x - 14x + 1/6x is -x
Given the expression
12 5/6x - 14x + 1/6x
Convert the mixed fractions into improper fractions as shown:
[tex]\frac{77}{6}x - 14x + \frac{1}{6}x[/tex]
Collect the like terms;
[tex]= \frac{77}{6} x+\frac{1}{6}x - 14x\\= \frac{77x+x}{6} - 14x\\= \frac{78x}{6} - 14x\\= 13x - 14x\\= -x[/tex]
Hence the result of the given expression is -x
Learn more here: https://brainly.com/question/17788156